Predicting habitat suitability of Illicium griffithii under climate change scenarios using an ensemble modeling approach - Anubhav Bhuyan; Amal Bawri; Bhrigu Prasad Saikia; Shilpa Baidya; Suhasini Hazarika; Bijay Thakur; Vivek Chetry; Bidya Sagar Deka; Pangkhi Bharali; Amit Prakash; Kuladip Sarma; Ashalata Devi (Scientific Reports)
Abstract Climate change is the most significant threat to global biodiversity, risking extinction for many species due to their limited adaptability to rapidly changing environmental conditions, such as temperature, precipitation, and other climate variables. Illicium griffithii, an endangered tree with ecological and medicinal value, remains understudied, particularly in Arunachal Pradesh. The aim of the study is to identify key environmental variables influencing the current distribution of I. griffithii and to predict the potential distribution under current and future climatic scenarios (SSP245 and SSP585). We used an ensemble modeling approach that integrates five species distribution models (SDMs). After multicollinearity test, we utilized fifteen environmental variables including bioclimatic variables, soil properties, topographical variables, and evapotranspiration to predict the potential distribution of I. griffithii. The study revealed that the current distribution is predominantly influenced by isothermality, nitrogen content at 0–5 cm depth, clay content at 0–5 cm depth, and seasonality of precipitation, with a total contribution rate of 42.6%. The ensemble model performed robustly and found to be excellent performance based on AUC of 0.94 and TSS of 0.83. The total highly suitable area for I. griffithii spans 722.72 km2 in the current scenario, primarily located in West Kameng, Tawang, and East Kameng districts. West Kameng stands out as the largest high-suitability area, which covers 592.83 km2 and contributing a substantial 82.03% of the total suitable area. However, under the SSP585 future climate scenario (2041–2060), projections reveal a concerning decline in highly suitable areas. The area is expected to shrink by over 5.05%, decreasing from 722.72 to 686.25 km2. The results have highlighted the vulnerability of I. griffithii under future climatic scenario. Hence, forest managers should prioritize conserving suitable habitats in West Kameng, Tawang, and East Kameng districts of Arunachal Pradesh by implementing habitat restoration, assisted migration and ex situ conservation strategies that can mitigate climate change impacts.